NIGERIA GHANA TRADE RELATIONS AND ITS IMPLICATIONS ON NIGERIA ECONOMY - Chidi Onyernama, Jude; Egwu, Chijioke; Stephen Chukwuma , Alumona; Bamidele , Joseph (CENTRAL ASIA AND THE CAUCASUS, 2024)
This study examined Nigeria and Ghana trade relations and implications on Nigeria’s economic development between 2010-2018. This research was based on two major objectives which were to examine the nature of trade relationship between Nigeria and Ghana, and ascertain the implications of Nigeria and Ghana trade relations on the economic development of Nigeria. In order to address the study objectives, basic literatures were reviewed thus: the concept of trade and international trade, contending perspectives on international trade, nature of trade relations between Nigeria and Ghana and implication of Nigeria-Ghana trade relations on Nigeria’s economic development were all reviewed in the course of this study, and the study hinged on the theory of complex interdependence as its theoretical base to analyze interconnectivity of nation’s with regards to trade implications. The study adopted the descriptive survey design and the population of the study comprised of traders from Nigeria and Ghana, male importers and female importers in Onitsha main market, as well as the senior staff of Federal Ministry of Trade and Investment. Data derived for the study were sorted, coded and analyzed using descriptive statistical tools such as frequency and percentages. Findings from the study showed that there exists a significant relationship between Nigerian and Ghana trades. Nigeria’s high level of liquidity serve as an important source of capital for Ghana. Ghana is a crucial one for the region, trade tis are particularly important, amongst. Hence, it was concluded that the Nigerian government needs to establish a regulating body to coordinate trade activities of Ghanaians in Nigeria. This is because Ghanaian traders is virtually everywhere in the country but information about their trade activities are fragmented. Based on the findings of the study, it was recommended that a technical team saddled with the responsibility of scrutinizing and evaluating agreements, treaties, memoranda etc. is established.